Intrasurgical Imaging of Subinternal Limiting Membrane Blood Diffusion in Terson Syndrome. (14th August 2014) - Iuliano, Lorenzo; Fogliato, Giovanni; Codenotti, Marco
Abstract : We report a case of Terson syndrome, providing the first intrasurgical imaging of subinternal limiting membrane blood diffusion in Terson syndrome. We highlight some remarkable in vivo anatomical findings that may give a contribution to the debate about its pathogenesis. Here we hypothesize that the subretinal space might be unlikely to be a primary source of intraocular hemorrhage, and we support the two generally accepted theories about blood diffusion from the retinal vasculature or from the perivascular spaces.